Nanometer‐Scale 1D Negative Differential Resistance Channels in Van Der Waals Layers - Qirong Yao; Jae Whan Park; Choongjae Won; Sang‐Wook Cheong; Han Woong Yeom (Advanced Science)
Abstract Negative differential resistance (NDR) is the key feature of resonant tunneling diodes exploited for high‐frequency and low‐power devices and recent studies have focused on NDR in van der Waals heterostructures and nanoscale materials. Here, strong NDR confined along a 1‐nm‐wide 1D channel within a van der Waals layer 1T‐TaS2 is reported. Using scanning tunneling microscopy, a double 1D NDR channel formed along the sides of a charge–density‐wave domain wall of 1T‐TaS2 is found. The density functional theory calculation elucidates that the strong local band‐bending at the domain wall and the interlayer orbital overlap cooperate to bring about 1D NDR channels. Furthermore, the NDR is well controlled by changing the tunneling junction distance. This result would be important for nanoscale device applications based on strong nonlinear resistance within van der Waals material architectures.